Evolution of the Circular Economy: Exploratory Network Analysis and State of The Art - Ana GALINA; Gabriel Lucas BANDEIRA; Ubiratã TORTATO (Communications of International Proceedings, 2023)
Circular Economy (CE) is a modern concept for achieving sustainable development goals, primarily to reduce resource wastage and increase efficiency. The concept has captivated scholars' attention across multiple fields, prompting exponential growth in research on this frontline. This article provides a comprehensive analysis of the evolution of the CE concept, focusing on its relationship with closed-loop supply chain (CLSC) and sustainability. This research aimed to analyze the evolution of CE by using exploratory network analysis, scientific contributions were retrieved from the Scopus database, totaling 133 papers without period restrictions, and generated data was analyzed by network analysis software CiteSpace. Finally, the results identified three main avenues representing the field and recommended readings to promote future qualitative, quantitative, and mixed methods studies
Keywords: Circular Economy; Closed-Loop Supply Chain; Evolution; Sustainability